2015
DOI: 10.1177/1555343415608974
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Shoot–Don’t Shoot Decision-Making Performance

Abstract: Soldiers are required to perform basic combat tasks, such as move, shoot, and communicate, and to make decisions under many environmental stressors, including continuous operations and information-processing tasks driven by C4ISR (Command, Control, Communications, Computers, Intelligence, Surveillance, and Reconnaissance) and other types of information systems. Knowledge requires information processing, and increased processing is usually the root cause of increased error. Friend-or-foe decision-making researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Specifically, the study of OiS performance allows researchers to understand decision making in a dynamic environment characterized by physical, cognitive, emotive, and temporal stressors (Neville & Salmon, 2016). These same characteristics are present in safety-critical domains—for example, firefighting (Klein, Calderwood, & Clinton-Cirocco, 2010) and military operations (Fiore, Ross, & Jentsch, 2012; Scribner, 2016). Furthermore, naturalistic research in sport, including the study of OiS, provides data on the way that individuals, teams, and systems conduct tasks, meet goals, and make decisions (Kermarrec & Bossard, 2014; Klein, 1998; Macquet, 2009; Macquet & Fleurance, 2007; Orasanu & Connolly, 1993).…”
mentioning
confidence: 88%
“…Specifically, the study of OiS performance allows researchers to understand decision making in a dynamic environment characterized by physical, cognitive, emotive, and temporal stressors (Neville & Salmon, 2016). These same characteristics are present in safety-critical domains—for example, firefighting (Klein, Calderwood, & Clinton-Cirocco, 2010) and military operations (Fiore, Ross, & Jentsch, 2012; Scribner, 2016). Furthermore, naturalistic research in sport, including the study of OiS, provides data on the way that individuals, teams, and systems conduct tasks, meet goals, and make decisions (Kermarrec & Bossard, 2014; Klein, 1998; Macquet, 2009; Macquet & Fleurance, 2007; Orasanu & Connolly, 1993).…”
mentioning
confidence: 88%
“…Study of performance shaping in aircraft maintenance engineering has shown that various factors can provoke unsafe behaviors in decisions (Hobbs, 2008). Affect is one such factor that has been researched in complex cognitive work in various real-world settings (e.g., Bowman & Rogers, 2016; Scribner, 2015) and may provide a window into the context surrounding decisions (Mosier & Fischer, 2010b) of the aircraft maintenance engineer. Varying in duration, cause, and consequence (Mosier & Fischer, 2010b), affect is a form of mental processing that reflects our internal subjective states and includes emotion, mood, and motivation (Cohen, Pham, & Andrade, 2006; Knutson, Katovich, & Suri, 2014).…”
Section: Affective Influences In Ndm In Aircraft Maintenance Engineeringmentioning
confidence: 99%
“…We chose to restrict our analysis to executive function tasks eliciting inhibitory control, for two primary reasons. First, inhibitory control is a crucial executive function that has been extensively linked to brain networks and highly relevant performance outcomes such as making shoot/don't-shoot decisions in law enforcement and military contexts (Biggs et al, 2015;Scribner, 2016;Biggs, 2021). Second, inhibitory control processes are effectively isolated from simple reaction time both behaviorally and neuroanatomically, with largely independent functional brain networks responsible for their performance (Seeley et al, 2007;Elton and Gao, 2014).…”
Section: Outcomes Of Interest: Reaction Time Executive Function and Perceptuo-motor Controlmentioning
confidence: 99%